The Effect of Humor Styles of Pregnant Women on Distress - Çapık, Ayla; Aydın, Ayşe; Taşğın, Zehra Demet; Pasinlioğlu, Türkan (Eastern Journal of Medical Sciences, 2019)
Objectives: This study was conducted to determine the effect of pregnant women’s humor styles on distress. Methods: A descriptive study was conducted on pregnant women who have applied to the Maternity Hospital Non-stress Test unit in the city of Erzurum from 1 August 2014 to 31 December 2014. A total of 301 pregnant women who met the inclusion criteria participated in the study. Data were collected using the Tilburg Pregnancy Distress Scale (TPDS) and Humor Styles Questionnaire (HSQ). For statistical analysis, percentages, means, and Pearson, r correlation were used. Results: There was a negative (r= -0.149, p=0.01) relationship between a self-enhancing humor style and distress level. A negative significant correlation was found between the partner involvement sub-dimension and participatory (r= -0.270, p=0.000), self-enhancing (r= -0.289, p=0.000) and self-destructive humor styles (r= -0.156, p=0.007). Furthermore, there was a significant positive correlation between an aggressive humor style and the negative emotion sub-dimension (r=0.136, p=0.018). Conclusion: As a result of the study, it was determined that the use of positive humor styles by pregnant women was higher and their distress levels were low. Furthermore, as the use of a positive humor style increased, the level of distress decreased.